Uji Ekstrak Kulit Buah Mangga Arum Manis dalam Etanol pada Tumbuh Kembang Escherichia coli dan Salmonella typhi - Mandike Ginting; Suprianto Suprianto; Siti Fatimah Hanum; Debi Meilani; Maya Sartika (LPPM STIKes Indah Medan, 2022)
Background: Antibacterial is a substance that can interfere with the growth or even kill bacteria by interfering with harmful microbial metabolites. The skin of the Harum Manis Mango (Mangifera indica L.var. arum sweet) contains flavonoid compounds which are known to have antibacterial activity. Objective: This study aimed to determine the antibacterial activity of the ethanol extract of Harum Manis Mango skin against the antibacterial activity of Escherichia coli and Salmonella typhi. Methods: The research method used in this study was the well diffusion method to determine the antibacterial activity of the ethanol extract of the Harum Manis mango skin Escherichia coli and Salmonella typhi using chloramphenicol 250 mg used as a comparison of antibacterial activity. Results: The results of the antibacterial activity of the ethanolic extract of Harum Manis mango skin against Escherichia coli showed the diameter of the inhibition zone as follows: 20% concentration (12.83 mm), 30% concentration (12.93 mm) and 40% concentration (13.91 mm), while against Salmonella typhi with a concentration of 20% (11.63mm), a concentration of 30% (12.5mm) and a concentration of 40% (13.5mm).Conclusion: The conclusion of this study is that the ethanol extract of the skin of the Harum Manis Mango (Mangifera indica L. var. arum sweet) has antibacterial activity against Escherichia coli and Salmonella typhi bacteria. The most effective concentration against Escherichia coli at concentration of 40% (13.91mm) and Salmonella typhi at a concentration of 40% (13.5mm) with strong inhibition.